Internet Gaming Disorder Explains Unique Variance in Psychological Distress and Disability After Controlling for Comorbid Depression, OCD, ADHD, and Anxiety - Pearcy, Benjamin; McEvoy, Peter; Roberts, Lynne (Mary Ann Liebert, Inc. Publishers, 2017)
This study extends knowledge about the relationship of Internet Gaming Disorder (IGD) to other established mental disorders by exploring comorbidities with anxiety, depression, Attention Deficit Hyperactivity Disorder (ADHD), and obsessive compulsive disorder (OCD), and assessing whether IGD accounts for unique variance in distress and disability. An online survey was completed by a convenience sample that engages in Internet gaming (N?=?404). Participants meeting criteria for IGD based on the Personal Internet Gaming Disorder Evaluation-9 (PIE-9) reported higher comorbidity with depression, OCD, ADHD, and anxiety compared with those who did not meet the IGD criteria. IGD explained a small proportion of unique variance in distress (1%) and disability (3%). IGD accounted for a larger proportion of unique variance in disability than anxiety and ADHD, and a similar proportion to depression. Replications with clinical samples using longitudinal designs and structured diagnostic interviews are required.